The Role of the Coupling of Educational Economic Management and Mental Health Education in the Psychological Construction of Student Movement - Yichao Zhao; Juan Chen; Jiancheng Li (Revista de Psicología del Deporte (Journal of Sport Psychology), 2024)
Sports can help students better understand their strengths in various aspects, make appropriate and objective evaluations of their abilities, personalities, and strengths, and avoid harsh and unreasonable delusions. They can also develop their own potential and experience the value of their existence. In order to carry out mental health education in physical education teaching and truly promote students' physical and mental health. This paper check the role of the coupling of educational economic management and mental health education in the psychological construction of student activism. A total of 300 questionnaires were distributed and 295 valid questionnaires were retrieved Based on a sampling survey of the psychological status of economic and management graduate students in some universities in city A, a comprehensive analysis, subgroup analysis, and internal structure analysis of the psychological status of economic and management graduate students were conducted using the Symptom Checklist 90 (SCL-90); The reasons for the psychological problems of graduate students in the field of economic management are the free and relaxed learning environment, the biased nature of the subject towards "literature", the abstract content of the subject, and the lack of mental health education for graduate students; The psychological health education for graduate students majoring in economic management should follow the principles of respect, timeliness, cooperation, prevention first, and differentiation, fully attach importance to psychological health education, establish and improve psychological prevention and emergency mechanisms, and do a good job in psychological health monitoring. Grasp the interrelationship between physical education teaching and mental health education, constantly update educational concepts, change teaching methods, and actively promote mental health education in physical education teaching.